2020
DOI: 10.1111/febs.15342
|View full text |Cite
|
Sign up to set email alerts
|

Messenger RNA delivery to mitoribosomes – hints from a bacterial toxin

Abstract: In mammalian mitochondria, messenger RNA is processed and matured from large primary transcripts in structures known as RNA granules. The identity of the factors and process transferring the matured mRNA to the mitoribosome for translation is unclear. Nascent mature transcripts are believed to associate initially with the small mitoribosomal subunit prior to recruitment of the large subunit to form the translationally active monosome. When the small subunit fails to assemble, however, the stability of mt-mRNA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 45 publications
2
11
0
Order By: Relevance
“…High-resolution northerns were carried out as described in [ 19 ] with modifications. Total RNA (5 µg) was separated by 15% polyacrylamide-8 M urea gels and electroblotted to Hybond ® -N+ nylon membranes (GE Healthcare Life Sciences, Marlborough, MA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…High-resolution northerns were carried out as described in [ 19 ] with modifications. Total RNA (5 µg) was separated by 15% polyacrylamide-8 M urea gels and electroblotted to Hybond ® -N+ nylon membranes (GE Healthcare Life Sciences, Marlborough, MA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Recent work by Bruni et al suggests that the stability of mt-mRNAs also depends on mitoribosome binding [ 111 ]. Depletion of the mt-LSU results in the downregulation of mt-mRNA levels, whereas the depletion of both mt-LSU and mt-SSU partially recovers mtRNA levels.…”
Section: Mitochondrial Rna Surveillance and Decaymentioning
confidence: 99%
“…The authors suggested that when solely mt-LSU is depleted, mt-SSU is available and capable of recruiting mature mt-mRNAs from the LRPPRC/SLIRP complex, thus depriving them of protection from degradation. Under normal conditions, the formation of the ribosome stabilizes mt-mRNAs and protects them from degradation [ 111 ].…”
Section: Mitochondrial Rna Surveillance and Decaymentioning
confidence: 99%
“…To ensure that all available high quality data on endogenous protein complexes enter this analysis, the manually curated BioGrid database entry on human ClpX protein associations was downloaded (Table S5). Among these known ClpX interactors, the ClpP-null fibroblasts and brain tissues exhibited consistent significant accumulations for the AAA+ ATPase ClpX itself, another AAA+ ATPase in mitochondria known as VWA8 (Von Willebrand Factor A Domain Containing 8) [39], the nucleoid component POLDIP2 (also known as PDIP38) (DNA Polymerase Delta Interacting Protein 2) [40], the mitochondrial RNA granule component LRPPRC (Leucine Rich Pentatricopeptide Repeat Containing) [41], the mitochondrial precursor RNA processing factor GRSF1 (G-Rich RNA Sequence Binding Factor 1) [42], the mitoribosomal tRNA translocation mediator GFM1 (G Elongation Factor Mitochondrial 1) [43], and the UPR mt sensor CHCHD2 (Coiled-Coil-Helix-Coiled-Coil-Helix Domain Containing 2) [24,44].…”
Section: Selected Dysregulations Are Reproducible In Brain Tissue and Reflect Direct Clpx Impact On Interactorsmentioning
confidence: 99%